The Fossil Birds of Peter Lund - Nascimento, Rafael; Silveira, Luís Fábio (Zootaxa, 2020)
The Danish naturalist Peter Wilhelm Lund (1801–1880), regarded as the father of Brazilian palaeontology and archaeology, is known mainly for his work with fossil mammals of Quaternary age from the limestone caves of the Lagoa Santa region in the state of Minas Gerais, southeastern Brazil. However, during one decade of fieldwork (1835–1844), he also collected a large number of remains of other animal groups from these caves. Birds were well represented and, following assessment by the Danish ornithologist Oluf Winge (1855–1889), most of the specimens collected by Lund belong to species still living in the area. Here we present an overview of the bird remains (fossil and recent), found by Lund and others in the region, we update their taxonomic attributions, and comment on the history of the material, making information previously published only in Danish available in English.